POST-STROKE REORGANISATION IN MOTOR CORTEX - DRAČA, SANJA; DRAČA, SANJA (Medicinski časopis, 2012)
Reorganization of the motor system after stroke, such as assessed by functional neuroimaging, has been the subject of considerable interest lately. To achieve a better understanding of the differences in functional recovery of patients with specific localisation of brain lesion numerous studies investigate the mechanisms underlying the changes in brain activation pattern after stroke, including the functional cerebral asymmetry as well as the transcallosal inter-hemispheric inhibition. Post-stroke reorganisation occurs in both the perilesional cortex and in cortex distant from the stroke, as well as in the motor cortex in unaffected contralateral hemisphere. The available observations suggest that recovery is the best when there is return of preferential activation toward the affected motor network. A shift of activation towards the primary motor cortex of the unaffected hemisphere suggests less efficient reorganisation, possibly even «maladaptive» plasticity.